4D printed tunable mechanical metamaterials with shape memory operations - Bodaghi, M; Liao, W H (Smart materials and structures, 2019)
The aim of this paper is to introduce tunable continuous-stable metamaterials with reversible thermo-mechanical memory operations by four-dimensional (4D) printing technology. They are developed based on an understanding on glassy-rubbery behaviors of shape memory polymers and hot/cold programming derived from experiments and theory. Fused decomposition modeling as a well-known 3D printing technology is implemented to fabricate mechanical metamaterials. They are experimentally tested revealing elastic-plastic and hyper-elastic behaviors in low and high temperatures at a large deformation range. A computational design tool is developed by implementing a 3D phenomenological constitutive model coupled with a geometrically nonlinear finite element method. Governing equations are then solved by an elastic-predictor plastic-corrector return map procedure along with the Newton-Raphson and Riks techniques to trace nonlinear equilibrium path. A tunable reversible mechanical metamaterial unit with bi-stable memory operations is printed and tested experimentally and numerically. By a combination of cold and hot programming, the unit shows potential applications in mimicking electronic memory devices like tactile displays and designing surface adaptive structures. Another design of the unit shows potentials to serve in designing self-deployable bio-medical stents. Experiments are also conducted to demonstrate potential applications of cold programming for introducing recoverable rolling-up chiral metamaterials and load-resistance supportive auxetics.